A comparative study on treatment seeking behaviour of geriatric population in rural and urban areas of district Kanpur, Uttar Pradesh - Ratan, Shiv; Nigam, Seema; Midha, Tanu; Chaudhary, Sachin (Indian Journal of Community Health, 2022)
Background: Aging is a complex and universal life process. Treatment seeking behaviour in elderly is affected by socio-economic factors and by affordability, availability and accessibility of healthcare. Objectives: To study treatment-seeking behaviour of the study subjects. To compare treatment seeking behaviour among rural and urban study subjects. Methods: This was a cross-sectional study conducted in the Kanpur district. Selection of villages in rural and mohallas in urban areas was done using a multistage random sampling technique. A total of 600 subjects were studied, including 400 from urban areas and 200 from rural areas. Elderly persons>60 years of age, both males and females were included in the study. Results: Overall, out of 600 study subjects, 59.8% were taking treatment in rural areas and in urban areas 77.6% were taking treatment. In urban areas, more females availed treatment compared to rural areas. Majority of study subjects (56.5%) sought treatment from a government hospital. Only 36% subjects had health insurance. Conclusion: In Urban areas more subjects availed treatment as compared to rural areas. Majority of subjects sought treatment from government health facilities. Lack of financial support and long waiting time were major reasons for not availing health care.